In Concordia. Eerste rij v.l.n.r.: Harinck, Eckhard, ?, ?, ?, Rijnders, Domela. Call number BG A61/411 uit archief: F. Domela Nieuwenhuis, map VI a 1 A,nr. 14
In Concordia. Eerste rij v.l.n.r.: Harinck, Eckhard, ?, ?, ?, Rijnders, Domela. Call number BG A61/411 uit archief: F. Domela Nieuwenhuis, map VI a 1 A,nr. 14.